A new class of ordınary generatıng functıons for bınary products of mersenne numbers and gaussıan numbers wıth parameters p and q - Saba, Nabiha; Boussayoud, Ali; Araci, Serkan; Kerada, Mohamed; Aracı, Serkan (Colgate University, 2023)
In this paper, we derive some new generating functions for the products of several special numbers including (p, q)-Fibonacci numbers, (p, q)-modified Pell numbers, and (p, q)-Jacobsthal Lucas numbers. We also give some new generating functions for the products of Mersenne and Gaussian numbers with parameters p and q. © 2023, Colgate University. All rights reserved.